Practical approach to nutrition and dietary intervention in pediatric food allergy. Issue 3 (6th February 2013) - Groetch, Marion; Nowak‐Wegrzyn, Anna
<x xml:space="preserve">Abstract</x> Although the need for nutritional and dietary intervention is a common thread in food allergy management, the type of food allergic disorder and the identified food allergen will influence the approach to dietary intervention. A comprehensive nutrition assessment with appropriate intervention is warranted in all children with food allergies to meet nutrient needs and optimize growth. However, dietary elimination in food allergy may also have undesirable consequences. Frequently, an elimination diet is absolutely necessary to prevent potentially life‐threatening food allergic reactions. Allergen elimination can also ease chronic symptoms, such as atopic dermatitis, when a food is proven to trigger symptoms. However, removing a food with proven sensitivity to treat chronic symptoms may increase the risk of an acute reaction upon reintroduction or accidental ingestion after long‐term avoidance, so it is not without risk. Additionally, it is not recommended to avoid foods in an attempt to control chronic symptoms such as AD and EoE when allergy to the specific food has not been demonstrated. Ultimately, allergen elimination goals are to prevent acute and chronic food allergic reactions in the least restrictive, but also the safest environment to supply a balanced diet that promotes health and growth and development in children.